Diagnostic and interventional radiology fundamentals of synovial pathology - Acanfora, Chiara; Bruno, Federico; Palumbo, Pierpaolo; Arrigoni, Francesco; Natella, Raffaele; Mazzei, Maria Antonietta; Carotti, Marina; Ruscitti, Piero; Di Cesare, Ernesto; Splendiani, Alessandra; Giacomelli, Roberto; Masciocchi, Carlo; et al. (Acta Biomedica Atenei Parmensis, 2020)
The synovial membrane is a specialized mesenchymal tissue that lines the diarthrodial joints surfaces, bursae, and tendon sheaths of the body. This article aims to provide an overview of the fundamentals of synovial tissue, with particular regard to the imaging findings of the main pathologic processes that can affect the synovia and the role of image-guided interventions.